2013
DOI: 10.2478/rrlm-2013-0025
|View full text |Cite
|
Sign up to set email alerts
|

Detection and serotyping of Listeria monocytogenes in some food products from North-East of Romania

Abstract: Listeria monocytogenes represents an important hazard to human health because it is capable of causing listeriosis, an atypical foodborne disease with a high fatality rate.The aim of this study was to detect and serotype Listeria monocytogenes in some food products (of animal and vegetable origin)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
(7 reference statements)
1
9
0
Order By: Relevance
“…After assessing all the information from the recovered publications, seventy-eight primary studies [6,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,…”
Section: Methodsmentioning
confidence: 99%
“…After assessing all the information from the recovered publications, seventy-eight primary studies [6,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,…”
Section: Methodsmentioning
confidence: 99%
“…The limited number of clinical strains can be explained by the fact that listeriosis is less common in Romania compared to other European countries, while food isolates of L. monocytogenes are usually unreported, thus making it difficult to gather a large collection of strains. Also, a recent study had shown that out of twenty five samples positive for L. monocytogenes by classical microbiological method, only 22 were confirmed by real-time PCR, suggesting that using only the standard method can lead to false results (14).…”
Section: Discussionmentioning
confidence: 99%
“…Cărare et al, [15] E. coli [13]. The readyto-eat (RTE) products are considered high-risk foods, because they support the growth of L. monocytogenes and do not require heat treatment before consumption.…”
Section: Carp-mentioning
confidence: 99%
“…Over the last decade, in Romania, there was a total of nine studies that published data on the isolation frequency of L. monocytogenes from a food matrix or food processing environment. The pathogen was recovered from a variety of food products, including raw (pork, beef, sheep, poultry, and snail) and mechanically processed meat, RTE, milk and dairy products, chicken carcasses, fish, and fresh salads [5,6,10,[14][15][16], with different prevalence values as highlighted in Table 1. Two studies were designed to identify L. monocytogenes predominantly in the food processing environment, including food contact and nonfood contact surfaces [14,17].…”
Section: Carp-mentioning
confidence: 99%
See 1 more Smart Citation